Perencanaan Sumber Daya Pendidik dan Tenaga Kependidikan di MTs. Tarbiyatul Huda - Intan Purnamasari; M. Fadhil Shobirin Mubarok; M. Goris Hoirul M.; Zidan Kholid Al-Fa’is; Rofiq Hidayat (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
The planning of educators and educational staff is a critical aspect in efforts to improve the quality of education at various levels, including at MTs Tarbiyatul Huda, Desa Jenggawah. This study aims to analyze the factors influencing HR planning, the processes carried out, and the planning system implemented at the school. The research employs a qualitative descriptive method, with data collection techniques including interviews, direct observation, and document studies. The findings show that HR planning at MTs Tarbiyatul Huda is influenced by academic needs, the competencies of educators and educational staff, financial support, government policies, technological changes, and collaboration between the school and its foundation. The HR planning process includes needs analysis, recruitment, continuous training, placement, and performance evaluation. Additionally, a competency-based and data-driven planning system is utilized to ensure the availability of qualified educators and staff. This article underscores the importance of multi-stakeholder collaboration and long-term HR development to sustain the quality of education. These findings are expected to serve as a reference for HR planning in similar educational institutions.